RANCANG BANGUN SISTEM PENGELOLAAN ARSIP SURAT MASUK DAN SURAT KELUAR BERBASIS WEB - Enggar Tegar Putra Pranata Sandra; Farihin Lazim (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The management of incoming and outgoing letters at the Office of Community Empowerment of Banyuwangi Regency is still carried out manually, resulting in inefficiencies and disorganized archiving. To address this issue, a web-based letter archiving information system was designed and developed. This study aims to produce an information system that facilitates structured and efficient document management. The development method used is the waterfall model. The results of this research indicate that the developed system meets user requirements and significantly improves the efficiency and accuracy of handling correspondence. By utilizing information technology, the archiving process becomes faster, more integrated, and error-resistant, thereby supporting better public service delivery.